Use of Deconvolution to Infer Past Diet in Austria and the USSR. Issue 1 (3rd April 2017) - Pelkonen, Henri; Cockshott, Paul
Abstract : Deconvolution is a technique commonly used in image processing. This study shows that it is possible to apply deconvolution to infer past nutritional levels if we know the recorded adult heights over a long time period. This study is a demonstration of how we can use deconvolution to investigate historical living standards. We apply it to investigating early Soviet and 18th to 19th century Austrian nutritional levels.